Replication Data for: Rural seed sector development through participatory varietal selection: Synergies and trade-offs in seed provision services and market participation among household bean producers in Western Uganda - Wilkus, Erin Lynn; Francesconi, Gian N.; Jager, Matthias (International Center for Tropical Agriculture, 2018)
This impact assessment provides empirical evidence from household producer surveys to test the assumptions surrounding the contribution of participatory varietal selection (PVS) activities on seed sector development. The purpose of this paper is to focus on household access and adoption of common bean varieties from seed provision services and local markets to determine if, and under what social conditions, PVS activities stimulated seed uptake and market participation. (2017-08-20)